2006
DOI: 10.1016/s1028-4559(09)60229-1
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Labor Induction with Titrated oral Misoprostol

Abstract: Titrated oral misoprostol is a safe and effective method of labor induction because the dosage can be adjusted according to individual response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…This was much lower than the incidence quoted by various authors. [8][9][10][11] The reason for this variation may be associated with the different dosage regimen of misoprostol used in different studies, as well as with different individual response to misoprostol. It is possible that the individual response of women to misoprostol may be dependent on drug absorption, peak levels reached and different action on uterus in different population groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was much lower than the incidence quoted by various authors. [8][9][10][11] The reason for this variation may be associated with the different dosage regimen of misoprostol used in different studies, as well as with different individual response to misoprostol. It is possible that the individual response of women to misoprostol may be dependent on drug absorption, peak levels reached and different action on uterus in different population groups.…”
Section: Discussionmentioning
confidence: 99%
“…This observation has prompted various studies using misoprostol in low doses as oral titrated solution and it has been found to be safer in terms of incidence of uterine hyperstimulation and fetal distress. [8][9][10][11] Based on these findings, this study was carried out in women with Bishop Score >6, using low dose titrated oral misoprostol solution for induction of labour. This method of induction was compared with titrated intravenous oxytocin in terms of labour outcomes, efficacy, adverse effects and neonatal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there will be little risk of maternal tachysystole or fetal hypoxia arising from titrated oral misoprostol. The small, frequent of titrated oral misoprostol administration [4,13,[15][16][17] in labor induction or augmentation was safe in clinical practice according to these findings.…”
Section: Lc/ms/msmentioning
confidence: 79%
“…In one pilot study, small, frequent (every 2 hours), titrated doses of oral misoprostol minimized the risk of uterine hyperstimulation and prevented fetal hypoxia [11,12]. Investigators developed an advanced approach with hourly oral misoprostol administration relative to uterine response for labor induction or augmentation at term or for terminating mid-trimester pregnancies [4,[13][14][15][16][17]; they achieved a high rate of success within 24 hours. According to the results of titration studies, misoprostol is an ideal candidate for labor induction and augmentation due to its convenience of administration and cervical ripening characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive uterine contractility resulting in fetal distress is a cause for concern 7–18 . Based on pharmacokinetics 19 and the findings of a previously reported clinical trial including lower incidence of uterine hyperstimulation and a shorter active phase interval, 20,21 it appears reasonable to use titrated oral misoprostol solution for labor induction in consideration of individual differences and responses. Because labor induction with titrated oral misoprostol solution is effective and safe, it has become the standard method used in our obstetric unit since 2004.…”
mentioning
confidence: 99%